2014
DOI: 10.1371/journal.pone.0115060
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Vulnerability in Older Cancer Patients: The ONCODAGE Prospective Multicenter Cohort Study

Abstract: BackgroundGeriatric Assessment is an appropriate method for identifying older cancer patients at risk of life-threatening events during therapy. Yet, it is underused in practice, mainly because it is time- and resource-consuming. This study aims to identify the best screening tool to identify older cancer patients requiring geriatric assessment by comparing the performance of two short assessment tools the G8 and the Vulnerable Elders Survey (VES-13).Patients and MethodsThe diagnostic accuracy of the G8 and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
255
8
20

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 472 publications
(301 citation statements)
references
References 41 publications
(60 reference statements)
18
255
8
20
Order By: Relevance
“…These results confirm that PS is a major prognostic factor for OS in lung cancer, as in other malignancies. The role of PS in this setting was recently confirmed in a large French prospective cohort study (20). As in other advanced cancers (21,22), the number of co-morbidities is also significantly associated with OS in advanced-stage NSCLC.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…These results confirm that PS is a major prognostic factor for OS in lung cancer, as in other malignancies. The role of PS in this setting was recently confirmed in a large French prospective cohort study (20). As in other advanced cancers (21,22), the number of co-morbidities is also significantly associated with OS in advanced-stage NSCLC.…”
Section: Discussionmentioning
confidence: 77%
“…It would be prudent to prioritise those tools with the best sensitivity (albeit less specific) and those with which physicians are familiar. With good sensitivity and independent prognostic value for 1-year survival, the G8 questionnaire (20) is currently one of the best screening tools for identifying older cancer patients requiring geriatric assessment, and we believe it should be broadly implemented in daily practice. Research must continue to refine the selection of older cancer patients for potentially life-threatening therapy (20,28).…”
Section: Discussionmentioning
confidence: 99%
“…The Vulnerable Elder Survey (VES-13) did correlate with a CGA in a pilot study of 50 patients with metastatic prostate cancer, as well as more diverse population of hematological and solid malignancies (21,22). The G8 instrument has been developed by the ONCODAGE project in France, and there are comparative data against the VES-13 suggests better sensitivity (23). A recent systematic review found that both the VES-13, and G8 (along with other instruments) did not have sufficient discrimination ability to replace the CGA (24).…”
Section: Discussionmentioning
confidence: 99%
“…An abnormal G8, VES-13, and Triage Risk Screening Tool have been associated with functional decline and poorer survival. 60,61,70 The Groningen Frailty Index has also been associated with worse survival. 46,71 Thus, it may not be unreasonable to consider performing a geriatric screen even in those centers in which a subsequent full geriatric assessment would not be possible.…”
Section: Geriatric Screening Toolsmentioning
confidence: 99%